The Effect of Lavender Essential Oil on Anxiety of Intra Uterine Device Insertion - M Mirmohammad ali; F Khazaie; M Modarres; F Rahimikian; P Rahnama; R Bekhradi; H Fallah Huseini (Institue of Medicinal Plants, ACECR, 2013)
Background: Intra uterine device is a safe, effective and reversible method of family planning. Unfortunately, IUD insertion associated with anxiety. The lavender essential oil has anti-anxiety and analgesic effect however itchr('39')s anti anxiety efficacy before intra uterine device insertion is to be evaluated. Objective: The present study was conducted to evaluate the anti-anxiety effect of lavender essential oil before intra uterine device insertion. Methods: Total 135 Iranian women candidate for intra uterine device insertion that had eligible criteria were randomly recruited into three lavender, placebo and control group. Data was collected by demographic questionnaire, spiel Berger questionnaire. The candidate apparent and acute anxiety was determined according to 20 questions present in Spiel Berger Questionnaire before and after aromatherapy just before intra uterine device insertion. The 20 questions were given four options including slight, moderate, high and very high with score 20 to 80. The womenchr('39')s were given a box containing a cotton ball soaked with three drops of lavender essential oil or sesame oil. The womenchr('39')s were asked to inhale the box for 5 minute from 7 to 10 centimeter from nose. The apparent and acute anxiety was determined in all three groups before and after aromatherapy just before intra uterine device insertion compared to each other. Data analysis was performed by SPSS software & descriptive & analytic statistics methods. Results: The average anxiety score was decreased in lavender group after aromatherapy compared to before aromatherapy (p<0.001) and also as compared to placebo and control groups (p<0.001). Conclusion: The Results of this study suggest that aromatherapy with inhalation of lavender essential oil is effective as anti- anxiety before IUD insertion.